2017
DOI: 10.1186/s12937-017-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and caffeine intake and male infertility: a systematic review

Abstract: BackgroundSemen quality, a predictor of male fertility, has been suggested declining worldwide. Among other life style factors, male coffee/caffeine consumption was hypothesized to influence semen parameters, but also sperm DNA integrity. To summarize available evidence, we performed a systematic review of observational studies on the relation between coffee/caffeine intake and parameters of male fertility including sperm ploidy, sperm DNA integrity, semen quality and time to pregnancy.MethodsA systematic lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 61 publications
1
63
0
4
Order By: Relevance
“…Few prospective studies also reported that male caffeine consumption was associated with reduced fecundability (70,73). Coffee intake might indulge in DNA breaks and aneuploidy (84). Curtis et al (65), Wesselink et al (85) also found a slight decrease in fecundability with coffee consumption.…”
Section: Q 2: Does Coffee Consumption Affect Male Fertility?mentioning
confidence: 98%
“…Few prospective studies also reported that male caffeine consumption was associated with reduced fecundability (70,73). Coffee intake might indulge in DNA breaks and aneuploidy (84). Curtis et al (65), Wesselink et al (85) also found a slight decrease in fecundability with coffee consumption.…”
Section: Q 2: Does Coffee Consumption Affect Male Fertility?mentioning
confidence: 98%
“…Several experimental studies have established that caffeine exhibit therapeutic effects against cardiovascular diseases, inflammation, including memory impairment and cognitive disorders such as dementia and Alzheimer's disease . Furthermore, research has also shown the link between consumption of caffeine and fertility . Consumption of high dose of caffeine has been linked with impairment in male fertility.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Furthermore, research has also shown the link between consumption of caffeine and fertility. [6] Consumption of high dose of caffeine has been linked with impairment in male fertility. Dorostghoal et al [7] reported that caffeine reduced testosterone levels and lowers germial epithelium height, weight of testis and diameter of seminiferous tubules.…”
Section: Introductionmentioning
confidence: 99%
“…In the meta-analysis, covering 57 cross-sectional studies which included 29914 participants, no significant effect of coffee on sperm quality was found [35]. Interestingly, a review of 28 observational studies, which involved 19 967 men, suggested that caffeine from coffee, tea and cocoa beverages did not have a negative impact on the quality of semen, as opposed to sweet drinks containing caffeine, the consumption of which in many studies was associated with a decreased semen volume and count, as well as with lower sperm concentration [38].…”
Section: Poor Nutritional Model Of Male Fertilitymentioning
confidence: 99%